2018
DOI: 10.1332/204674317x15071998786492
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child attachment as a mechanism of intergenerational (dis)advantage

Abstract: Parent-child attachment as a mechanism of intergenerational (dis)advantage. Families, Relationships and Societies, 7(2), 265-284.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 100 publications
0
11
0
1
Order By: Relevance
“…Having a ‘secure’ or healthy attachment with the parent provides children with a ‘secure base’ from which they can comfortably leave and explore (Bowlby, 1979: 132) and provides a template for future relationships with others (Holmes, 1993: 77). In terms of parenting behaviours that foster this secure attachment, this theory emphasises the importance of sensitivity and responsiveness, for example holding and comforting a child when they cry, which enables the child to feel secure and also teaches them they can ‘safely express negative emotion’ and the parent will respond in a way that makes them feel better (Moullin et al, 2014: 9). Studies informed by attachment theory have found that children who have a secure bond with their main caregiver develop healthier psychological dispositions (such as trusting others, not being overly dependent or self-reliant) (Bowlby, 1979) as well as better physical health, cognitive and language outcomes (Moullin et al, 2014: 11).…”
Section: Analytical Approachmentioning
confidence: 99%
“…Having a ‘secure’ or healthy attachment with the parent provides children with a ‘secure base’ from which they can comfortably leave and explore (Bowlby, 1979: 132) and provides a template for future relationships with others (Holmes, 1993: 77). In terms of parenting behaviours that foster this secure attachment, this theory emphasises the importance of sensitivity and responsiveness, for example holding and comforting a child when they cry, which enables the child to feel secure and also teaches them they can ‘safely express negative emotion’ and the parent will respond in a way that makes them feel better (Moullin et al, 2014: 9). Studies informed by attachment theory have found that children who have a secure bond with their main caregiver develop healthier psychological dispositions (such as trusting others, not being overly dependent or self-reliant) (Bowlby, 1979) as well as better physical health, cognitive and language outcomes (Moullin et al, 2014: 11).…”
Section: Analytical Approachmentioning
confidence: 99%
“…In recent years, a shift from the focus on primarily negative aspects of maternal mental health, such as symptoms of depression, anxiety, or states of distress and child maladaptation to positive maternal health and child resilience-inducing processes signals a growing awareness of the vital necessity to move at least some of the available research resources toward more preventative approaches ( Feldman, 2020 ; Phua et al, 2020 ). Similarly, the emerging evidence for links between the capacity to engage in trustful relations—being securely attached—and physical health ( Puig et al, 2013 ; Holt-Lunstad, 2018 ; McDade and Harris, 2018 ; Ehrlich and Cassidy, 2019 ) as well as the large proportion of the general population showing deficits in that very capacity ( van Ijzendoorn and Sagi-Schwartz, 2008 ; Bakermans-Kranenburg and van IJzendoorn, 2009 ; Moullin et al, 2014 ) gives even greater urgency to confirm and implement scalable interventions. Supporting parents to engage in extended physical contact with their full-term healthy infants appears to bring about many of the animal OT- and sensory-stimulation-related effects and furthermore may be a comparatively low-cost and thus scalable intervention ( Williams and Turner, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Links between OT, maternal attachment representations, maternal caregiving behavior, and infant attachment outcomes ( Strathearn et al, 2009 ; Shah et al, 2010 ; Atzil et al, 2011 ; Galbally et al, 2011 ) suggest that population estimates of infant and adult insecure attachment might serve as a meaningful proxy. On this basis, approximately 40% of the general population will suffer from suboptimum OT systems/insecure attachment ( van Ijzendoorn and Sagi-Schwartz, 2008 ; Bakermans-Kranenburg and van IJzendoorn, 2009 ; Moullin et al, 2014 ). Insecure attachment/suboptimum social functioning is increasingly recognized for its role in human physical and psychological disease ( Puig et al, 2013 ; Holt-Lunstad, 2018 ; McDade and Harris, 2018 ; Ehrlich and Cassidy, 2019 ) as is the prophylaxis of the capacity to have positive social connections in the face of childhood trauma ( Garner et al, 2012 ).…”
Section: Extended Parent–infant Physical Contactmentioning
confidence: 99%
“…Diğer bir ifade ile anne-bebek arasındaki bağlanma örüntüsünün ve ebeveynlerin evlilik uyumlarının nesiller arası aktarımının olduğu tartışılmaktadır (Jones et al 2015). Örneğin, Moullin et al (2018) derleme çalışmasında anne babaların bağlanma örüntüleri ile çocuklarının bağlanma örüntüleri arasında yüksek ilişki bulmuştur. Ayrıca, güvenli bağlanan ebeveynlerin çocuklarının ilerleyen yaşlarda daha iyi eğitim seviyesine sahip olduğu, gelir düzeylerinin daha yüksek olduğu, yakın ilişkilerde daha az çatışma yaşadıkları belirtilmiştir.…”
Section: Fig 1 Modelunclassified